(untitled) (Journal of Economic Research & Business Administration, 2016)
Risk management is a very important element of small and medium-sized enterprises activities. The research directed to the existing problems in the risk management and the search for the most effective ways of im-proving or supplementing the risk management system at the enterprises of Kazakhstan. In this article, we analyze the dynamics of the development of enter-prises in Kazakhstan, indicators of small and medium businesses in other countries, as well as the reasons for the failure of projects in RK.